Long-term retention of knowledge after a distance course in medical informatics at Charles University Prague - Naidr, J P; Adla, T; Janda, A; Feberová, J; Kasal, P; Hladíková, M (Teaching and learning in medicine, 2004)
BACKGROUND: Distance education is instructional delivery that does not constrain the student to be physically present in the same location as the instructor. The electronic distance learning called e-learning has evolved with the development of computer technologies and electronic communication. PURPOSE: Before setting the distance way of teaching as a standard part of medical schools' curricula, the impact of number of factors on the effectiveness of this way of teaching should be considered. METHODS: A group of 38 students went through a distance course of medical informatics. The course consisted of 10 lessons. At the end of the course the students sat for a final test that contained 60 multiple-choice test questions. There was always one correct answer. Time limit for test completion was 60 minutes. After 12 months, 31 students from the original group sat for the same test. The topics of the course were not repeated in the meantime. The students were not aware that their knowledge would be tested after 1 year. RESULTS: The average retention of knowledge expressed as a percentage of the students' performance in the first test was 66.8%. The knowledge retention correlated significantly with the statement "I liked the online course more than the classroom course" and positively with the number of hours spent with the computer weekly. CONCLUSIONS: Retention of knowledge after the electronic distance course after 12 months is close to 67%. Other results indicate that we can expect better retention of knowledge from independent, responsible, and positively motivated students who can easily operate information technologies.
Keywords: studenti lékařství; Students, Medical; Education, Distance; Medical Informatics; Health Knowledge, Attitudes, Practice; studium lékařství pregraduální; Česká republika; lékařská informatika; Computer-Assisted Instruction; Czech Republic; Time Factors; lidé; zdraví - znalosti, postoje, praxe; Humans; Education, Medical, Undergraduate; časové faktory; Educational Measurement; výuka - hodnocení; počítačem řízená výuka; distanční studium